Pengaruh Kualitas Layanan dan Digital Marketing Terhadap Minat Beli Studi Kasus pada Toko Af Family PPMT - Yusril Abdul Ghani; Sahara; Tedi Kustandi (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study aims to analyze the influence of service quality and digital marketing on consumers’ purchase intention at Toko Af Family, Majalengka. The research was motivated by the decline in sales and low consumer interest, which were assumed to be influenced by suboptimal service and digital promotion. The study employed a quantitative approach with a causal associative design. The population consisted of all consumers of Toko Af Family, with a sample of 97 respondents determined using the Slovin formula. Data were collected through a five-point Likert scale questionnaire and analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression with the help of SPSS 26. The findings indicate that service quality has a positive and significant effect on purchase intention, digital marketing also has a positive and significant effect, and both variables simultaneously explain 53.4% of the variance in purchase intention. These results highlight the importance of improving service quality and optimizing digital marketing strategies to strengthen the competitiveness of local retailers.